Association of Some Anthropometric and Hemodynamic Variables with Glycemia - Milagros Lisset León Regal; Jacqueline Zamora Galindo; Mikhail Benet Rodríguez; Luis Alberto Mass Sosa; Cynthia Morales Pérez; Lázaro Hermes González Otero (Universidad de las Ciencias Médicas de Cienfuegos, 2019)
Foundation: various sources claim that there are differences in some anthropometric and hemodynamic variables between individuals with normal, risk and pathological glycemia, which makes necessary to show new evidence. Objective: to determine the relationship between anthropometric and hemodynamic variables with the glycemia figures in individuals of the Cienfuegos municipality in 2010. Methods: a correlational cross-sectional descriptive study was carried out. The sample consisted of 925 individuals. The variables analyzed were: age, sex, skin color, abdominal waist, body mass index, systolic, diastolic and mean blood pressure, cardiovascular reactivity index and glycemia. Nonparametric statistical tests were applied to evaluate the correlation between fasting blood glucose and the study variables, with a significance of 99 %. The results are presented in tables and graphs. Results: there was a predominance of white skin color and female gender and individuals between 35-44 years represented the highest percentage of the sample. Patients with risk glycemia and diabetics had an increase in the study variables above normal. Conclusions: there is a positive correlation between glucose concentration and the analyzed variables, which explains anthropometric and hemodynamic imbalances in patients with glycemia risk and pathology.